Pengembangan media smart powerpoint berbasis animasi dalam pembelajaran fisika - Irnin Agustina Dwi Astuti; Maria Dewati; Indica Yona Okyranida; Ria Asep Sumarni (Navigation Physics : Journal of Physics Education, 2019)
The topic of motion in physics is one material that requires a real explanation so that it is easily understood by students. One of the strategies is to provide powerpoint animation learning media. This study aims to produce learning media that are suitable for use in learning. This research is a development research (R & D) with model of Borg and Gall. The instrument of data collection is a validation questionnaire. Data were analyzed by qualitative descriptive and descriptive statistical analysis. The results of this study indicate the media feasibility of learning aspects of learning, with an average score of 3.11 or 77.75% and included in the criteria "sufficiently valid" to be used in learning at school.